Comércio, política e ciência nas exposições internacionais: o Brasil em Turim, 1911. Parte 1 - SANJAD, Nelson Rodrigues (Universidade Federal do Pará, 2018)
The article analyses the participation of the Brazilian State of Pará at the International Exposition of Industry and Work in Turin, 1911. The Pará exhibition brought together especially products from the extractivism and may be characterized by its scientific discourse, materialized mainly by the presence of a renowned scientist in the organizing committee, the Swiss botanist Jacques Huber (1867-1914), then Director of the Goeldi Museum in Belém. The reasons to highlight science in the Pará exhibition and for the involvement of a scientist in a commercial event are studied through the following questions: the diplomatic strategies that took place in Turin; the role given to science in the organization of this world’s fair; and the dissonant forces in the representation of Brazil, noticeable on the difficulty of drawing up a national discourse and on the distance between a deeply unequal society and the image that was built of this same society. (The second part of this article will be published in next Varia Historia, vol. 32, n. 58, january-april 2016)